Artificial intelligence and its impact on the legal fraternity - Rajendra, Josephine Bhavani; S.Thuraisingam, Ambikai (UUM Press, 2022)
The article endeavors to analyze the implications of artificial intelligence (AI) in the legal fraternity. There have been various reports on the impact and challenges of AI in the legal fraternity in recent years. AI is used to perform legal work previously completed solely by human lawyers. The rise of AI technology has caused a great deal of apprehension among members of the legal fraternity both in Malaysia and globally. AI promises to disrupt the substratum of how legal work is practiced and delivered. Nevertheless, there are implications encountered by the legal fraternity in adopting AI in legal practice such as ethical responsibility, algorithm bias, data privacy and the lack of regulations for AI. The doctrinal method was employed in conducting this study. The primary objective of this article is to evaluate the implications of AI adoption in the legal fraternity and to propose recommendations for better integration of AI in the legal industry.